SOURCES OF ENVIRONMENTAL THREATS IN EL-ORO PROVINCE (ECUADOR) - Ramos, Maria Cristina; Petruk, Roman; Ishchenko, Vitalii; Petruk, Galyna (Scientific Works of Vinnytsia National Technical University, 2017)
The authors analyze the impact of environmental threats in El-Oro province and also analyze factors of environmental threats dissemination, for example pesticides in surface waters, leaching of soil. The article aims to identify sources of environmental threats and their impact on environment and public health, as well as to develop the measures for reducing the risk of potential threats.